An Empirical Evaluation Of Hedge Fund Managerial Skills Using Bayesian Techniques - Muteba Mwamba, John Weirstrass (Asian Academy of Management (AAM), 2017)
This paper makes use of the Bayesian method to evaluate hedge fund managers’ selectivity, market timing and outperformance skills separately, and investigates their persistence from January 1995 to June 20101. We divide this sample period into four overlapping sub-sample periods that contain different economic cycles. We defne a skilled manager as a manager who can outperform the market in two consecutive sub-sample periods. We employ Bayesian linear CAPM and Bayesian quadratic CAPM to generate skill coeffcients during each sub-sample period. We found that fund managers who possess selectivity skills can outperform the market at 7.5% signifcant level if and only if the economic conditions that governed the fnancial market during the period between sub-sample period2 and subsample period3 remain the same.